FLIP-ANGLE EFFECTS IN FOURIER-TRANSFORM EPR-SPECTRA OF SPIN-CORRELATED RADICAL PAIRS - Timmel, C; Hore, P (1994)
The EPR spectra of spin-correlated radical pairs in pulse-acquire Fourier-transform experiments are explored by means of spectral simulations. In particular, the dependence on the flip-angle (α) of the microwave pulse is examined. The spectra are seen to be linear combinations of two sub-spectra, with amplitudes proportional to sin α and sin 2α, which have distinctive shapes both for idealised dipolar-coupled radical pairs with isotropic g-values and no hyperfine couplings, and under the conditions found for radical pair intermediates in photosynthetic energy conversion. In cases of poor resolution, the two sub-spectra contain independent information on the structure and interactions of the radical pairs, which should supplement data available from the more routine time-resolved continuous-wave experiment. © 1994.